Ginger (Zingiber officinale) for Nausea and Vomiting of Pregnancy: A Narrative Review - Zahira Maulidina Sari Devi; Fika Churun Aini; Puspita Triawangi Putri; Qatrunnada Naqiyyah Khusmitha (Faculty of Medicine, Universitas Negeri Surabaya, 2025)
Nausea and vomiting of pregnancy (NVP) affect approximately 70–80% of pregnant women, particularly during the first trimester, and can substantially reduce maternal quality of life. Concerns regarding the potential adverse effects of pharmacological antiemetics have increased interest in complementary therapies, including ginger (Zingiber officinale), as a non-pharmacological alternative. This narrative review aimed to synthesize recent evidence regarding the effectiveness, safety, dosage, and mechanism of action of ginger in managing NVP. A literature search was conducted using PubMed and ScienceDirect to identify articles published between 2020 and 2025. Five eligible studies, comprising cross-sectional studies, literature reviews, an umbrella review, and a comprehensive evidence-based review, were included and narratively synthesized. The findings consistently demonstrated that ginger effectively reduces nausea during pregnancy, although its effect on vomiting is less consistent. Recommended doses ranged from 0.5 to 3 g/day, administered mainly as oral capsules or ginger tea. Ginger exerts its antiemetic effects by inhibiting serotonin (5-HT3) receptors, enhancing gastric emptying, and providing anti-inflammatory and antioxidant activities. Overall, ginger has a favorable safety profile when consumed within the recommended dosage, although caution is advised in pregnant women with bleeding disorders or those receiving anticoagulant therapy. Ginger may therefore be considered an effective and generally safe complementary therapy for managing mild to moderate NVP; however, further high-quality clinical studies are needed to establish standardized dosage recommendations and strengthen the evidence supporting its routine clinical use.